Civic engagement during crisis: Does volunteering buffer the impact of trauma on worsening physical and mental health? - Sharon Stein Merkin; Liat Orenstein (SSM - Mental Health)
Introduction: Experiences of trauma impact mental and physical health; civic engagement, including volunteering, may alleviate trauma-related health consequences. Research objective: Examine the association between war-related trauma and worsening health outcomes, and how volunteering may buffer the harmful health effects of trauma. Methods: We administered a population-based survey of Israelis ages 18+, with a total sample of n = 1129. Trauma exposure was assessed since the war onset (October 7, 2023) and included direct (witnessed/experienced) and indirect (experienced by family/close friend) violent trauma, displacement (experienced), and seeking sheltering frequently from rocket attacks (experienced). Data on volunteering type and intensity was collected; health outcomes included self-reported worse physical health, mental health, sleep and initiating ≥3 negative health behaviors since October 7th. Results: Multivariable results showed robust associations between indirect violent trauma, displacement and worsening health outcomes and some association between direct violent trauma and worse sleep and behaviors, after adjustment for co-occurring trauma exposure, sociodemographic factors, social wellbeing and volunteering. The association between displacement and worse mental health was limited to non-volunteers. We also found indication of health risk associated with engaging in ≥3 volunteering activities. Conclusions: Results show physical and mental health effects of exposure to war-related trauma and suggest that volunteering may prevent worsening mental health but may contribute to worsening physical health. Research is needed to determine the longer-term effects of volunteering post-trauma. Focusing on a social intervention, civic engagement, to mitigate pathological processes related to traumatic stress may lead to innovative ways to promote wellbeing in times of crisis.